CCS Resource Management in Networked HPC Systems - Keller, Axel; Reinefeld, Alexander (Proc. Heterogenous Computing Workshop (HCW) at IPPS)
CCS is a resource management system for parallel high-performance computers. At the user level, CCS provides vendor-independent access to parallel systems. At the system administrator level, CCS offers tools for controlling (i.e, specifying, configuring and scheduling) the system components that are operated in a computing center. Hence the name "Computing Center Software". CCS provides: hardware-independent scheduling of interactive and batch jobs; partitioning of exclusive and non-exclusive resources; open, extensible interfaces to other resource management systems; a high degree of reliability (e.g. automatic restart of crashed daemons); fault tolerance in the case of network breakdowns. The authors describe CCS as one important component for the access, job distribution, and administration of networked HPC systems in a metacomputing environment.

Specifying Resources and Services in Metacomputing Environments - Brune, Matthias; Gehring, Jörn; Keller, Axel; Monien, Burkhard (Parallel Computing)
With a steadily increasing number of services, metacomputing is now gaining importance in science and industry. Virtual organizations, autonomous agents, mobile computing services, and high-performance client–server applications are among the many examples of metacomputing services. For all of them, resource description plays a major role in organizing access, use, and administration of the computing components and software services. We present a generic Resource and Service Description (RSD) for specifying the hardware and software components of (meta-) computing environments. Its graphical interface allows metacomputer users to specify their resource requests. Its textual counterpart gives service providers the necessary flexibility to specify topology and properties of the available system and software resources. Finally, its internal object-oriented representation is used to link different resource management systems and service tools. With these three representations, our generic RSD approach is a key component for building metacomputer environments.

The Latency-of-Data-Access model for Analyzing Parallel Computation - Simon, Jens; Wierum, Jens-Michael (Information Processing Letters - Special Issue on Models of Computation)

A Closer Step towards Management of Metacomputing-Resources - Brune, Matthias; Hellmann, Christian; Keller, Axel (Proc. Workshop Hypercomputing at ITG/GI-Conference Architekur von Rechensystemen)

Workload Analysis of Computation Intensive Tasks: Case Study on SPEC CPU95 Benchmarks - Simon, Jens; Weicker, Reinhold; Vieth, Marco (Proc. European Conf. on Parallel Processing (Euro-Par))

Experiences with a SCI Multiprocessor Workstation Cluster - Heinz, Oliver; Simon, Jens (Proc. Int. Conf. on Architecture of Computing Systems (ARCS))

SCI multiprocessor PC cluster in a WindowsNT environment - Simon, Jens; Heinz, Oliver (Proc. Workshops im Rahmen der 14. ITG/GI-Fachtagung Architektur von Rechensystemen)

Embedding SCI into PVM - Fischer, Markus; Simon, Jens (Proc. European Parallel Virtual Machine / Message Passing Interface Users’ Group Meeting (EuroPVM/MPI))

The MOL Project: An Open, Extensible Metacomputer - Reinefeld, Alexander; Baraglia, Ranieri; Decker, Thomas; Gehring, Jörn; Laforenza, Domenico; Ramme, Friedhelm; Römke, Thomas; Simon, Jens (Proc. Heterogenous Computing Workshop (HCW))

Sequential Performance versus Scalability: Optimizing Parallel LU-Decomposition - Simon, Jens; Wierum, Jens-Michael (Proc. Int. Conf. on High-Performance Computing and Networking (HPCN-Europe))

Performance Prediction of Benchmark Programs for Massively Parallel Architectures - Simon, Jens; Wierum, Jens-Michael (Proc. Annual Int. Conf. on High-Performance Computers (HPCS))

Accurate Performance Prediction for Massively Parallel Systems and its Applications - Simon, Jens; Wierum, Jens-Michael (Proc. European Conf. on Parallel Processing (Euro-Par))

On Accurate Performance Prediction for Massively Parallel Systems and its Applications - Simon, Jens; Wierum, Jens-Michael

Implementation of a Parallel and Distributed Mapping Kernel for PARIX - Röttger, Markus; Schroeder, Ulf-Peter; Simon, Jens (Proc. Int. Conf. on High-Performance Computing and Networking)

An Efficient Mapping Library for Parix - Römke, Thomas; Röttger, Markus; Schroeder, Ulf-Peter; Simon, Jens (Proc. ZEUS Workshop on Par. Programming and Computation)

On Efficient Embeddings of Grids into Grids in PARIX - Römke, Thomas; Röttger, Markus; Schroeder, Ulf-Peter; Simon, Jens (Proc. European Conf. on Parallel Processing (Euro-Par))

SparcStation SCI-Interface - Gehring, Jörn; Simon, Jens

Parallel CG Poisson Solver for PowerPC 601 - Blazy, Stephan; Dralle, Uwe; Simon, Jens (PowerXplorer User Report - Applications and Projects on the Parsytec PowerXplorer Parallel Computer)

Leistung eines Parallelrechners auf Basis des PowerPC-Prozessors - Simon, Jens (Parallele Datenverarbeitung aktuell: TAT '94)

Benutzung virtueller Topologien unter PARIX - Simon, Jens